PEMBENTUKAN KONSEP DIRI REMAJA - Syahraeni, Andi (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2020)
The concept of self is an evaluation of a specific domain of self. Teenagers can make a self-evaluation of various domains in their academic life Self-concept is a very important and decisive factor in interpersonal communication. Self-concept can affect one’s thinking ability. self-concept has three components, namely Perceptual or physical self-concept is a person’s self-image related to his physical appearance, including the impression or attraction that he has for others. This component is also referred to as physical self-concept. Conceptual or psychological self-concept which is also referred to as psychological self-concept, psychological self-concept is a picture of a person, his ability or disability, his future, and includes the quality of his life adjustment, honesty, self-confidence, freedom and courage. Attitudinal are one’s feelings towards him, attitude towards his present and future existence, his attitude towards a sense of self-worth and a sense of pride. self-concept can be influenced by various factors, both factors from within the individual, such as physical conditions, family circumstances, people’s perceptions of individual self, parents’ demands on individuals, people who are close in the individual environment, and their perception of success and failure.